Rozwój greckokatolickiej sieci paraﬁalnej dekanatu kalnickiego w XVIII wieku - Wodzianowska, Irena (Studia Geohistorica, 2017)
Basing on the materials collected during canonical visitations, an attempt was made to reconstruct the process of changing the borders of the Kalnik deanery since the moment of its establishment at the beginning of the 18th century till it was incorporated into the structures of the Eastern Orthodox Church after the partition of the Second Republic of Poland. A dynamic development of the network of parishes, especially in the first half of the century, was caused by the growth of settlement and the care that the Orthodox Church took about the access of the faithful to the sacraments. Together with an increasing number of Orthodox churches the deanery was re-reorganized a few times and the parishes were incorporated into the new units of the church administration. Th e population growth additionally led to a greater number of Orthodox churches in the towns and to the divisions inside the existing parishes as well as to the foundation of new ones in their territory. Therefore, the territorial structure of deanery was subject to changes. Within 60 years (1731– 1793) the parishes belonging to the Kalnik deanery were included in the structures of seven other deaneries, and the area of the deanery itself decreased from seven regions of today’s Vinnytsia Oblast to two. Before the partitions of Poland, an optimum number of Orthodox churches was reached for that area and for the demographic structure of the population while the deanery’s borders got stabilized.